Home treatment of patients with low-risk pulmonary embolism with the oral factor Xa inhibitor rivaroxaban - Barco, Stefano; Lankeit, Mareike; Binder, Harald; Schellong, Sebastian; Christ, Michael; Beyer-Westendorf, Jan; Duerschmied, Daniel; Bauersachs, Rupert; Empen, Klaus; Held, Matthias; Schwaiblmair, Martin; Fonseca, Cândida; Jiménez, David; Becattini, Cecilia; Quitzau, Kurt; Konstantinides, Stavros (Thrombosis and Haemostasis, 2016)
Pulmonary embolism (PE) is a potentially life-threatening acute cardiovascular syndrome. However, more than 95 % of patients are haemodynamically stable at presentation, and among them are patients at truly low risk who may qualify for immediate or early discharge. The Home Treatment of Pulmonary Embolism (HoT-PE) study is a prospective international multicentre single-arm phase 4 management (cohort) trial aiming to determine whether home treatment of acute lowrisk PE with the oral factor Xa inhibitor rivaroxaban is feasible, effective, and safe. Patients with confirmed PE, who have no right ventricular dysfunction or free floating thrombi in the right atrium or ventricle, are eligible if they meet none of the exclusion criteria indicating haemodynamic instability, serious comorbidity or any condition mandating hospitalisation, or a familial/social environment unable to support home treatment. The first dose of rivaroxaban is given in hospital, and patients are discharged within 48 hours of presentation. Rivaroxaban is taken for at least three months. The primary outcome is symptomatic recurrent venous thromboembolism or PE-related death within three months of enrolment. Secondary outcomes include quality of life and patient satisfaction, and health care resource utilisation compared to existing data on standard-duration hospital treatment. HoT-PE is planned to analyse 1,050 enrolled patients, providing 80 % power to reject the null hypothesis that the recurrence rate of venous thromboembolism is >3 % with α≤0.05. If the hypothesis of HoT-PE is confirmed, early discharge and out-of-hospital treatment may become an attractive, potentially cost-saving option for a significant proportion of patients with acute PE.
Keywords: Pulmonary embolism; home treatment; management trial; rivaroxaban; risk stratification